Genetic study with Heliconia psittacorum and interspecific hybrids - Rocha,Francisco Herverton Albuquerque (2010)
A genetic study of seven cultivars of H. psittacorum and Heliconia interspecific hybrids was carried out. The heritability estimate and genetic variation coefficient were highest for stem diameter (SD) (99.32% and 56.90%, respectively) and for CVg/CVe (1.85), indicating a favorable situation for selection. The genetic correlations of SD with days to inflorescence emergence (DIE) (0.64), period from shoot emergence to stem cut (CYCLE) (0.63) and stem weight (SW) (0.96) showed that the time from inflorescence emergence to cut is longer and the stem weight is greater for genotypes with larger stem diameter. Inflorescence length (IL), SD and DIE were the most important traits, accounting for 99.55% of the total variation. For SD and IL, the repeatability values exceeded 0.60 and for SD, SW, DIE and IL the coefficients of determination exceeded 93%.